2008
DOI: 10.1021/jp802621w
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra of Triiodomesitylene: Combination of DFT Calculations and Experimental Studies. Effects of the Environment

Abstract: A study of the internal vibrations of triiodomesitylene (TIM) is presented. It is known from X-rays diffraction at 293 K that the molecule has nearly D(3h) symmetry because of the large delocalization of the methyl protons. By using Raman and infrared spectra recorded at room temperature, a first assignment is done by comparing TIM vibrations with those of 1,3,5-triiodo- and 1,3,5-trimethyl-benzene. This assignment is supported by DFT calculations by using the MPW1PW91 functional with the LanL2DZ(d,p) basis se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In several papers devoted to IR and Raman spectroscopies and reported by some of us, it has been shown that using the so-called anharmonic oscillator (AO) level to compute vibrations is much more accurate than the use of an ad-hoc scale factors and so for a relative weak computational cost. 7,[9][10][11][12][13][14][15][16]24 Furthermore, only full account of both mechanical and electrical anharmonicity allows us to assign the whole IR and Raman spectra (including overtones and combination bands). 11,13 So cubic and semidiagonal quartic force constants have been computed by finite differences of analytical Hessians at the B3LYP-D3 to obtain anharmonic frequencies with the GVPT2 model taking into the proper account possible Fermi and Darling−Dennison resonances, and the symmetry of the molecule.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several papers devoted to IR and Raman spectroscopies and reported by some of us, it has been shown that using the so-called anharmonic oscillator (AO) level to compute vibrations is much more accurate than the use of an ad-hoc scale factors and so for a relative weak computational cost. 7,[9][10][11][12][13][14][15][16]24 Furthermore, only full account of both mechanical and electrical anharmonicity allows us to assign the whole IR and Raman spectra (including overtones and combination bands). 11,13 So cubic and semidiagonal quartic force constants have been computed by finite differences of analytical Hessians at the B3LYP-D3 to obtain anharmonic frequencies with the GVPT2 model taking into the proper account possible Fermi and Darling−Dennison resonances, and the symmetry of the molecule.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…Computations have been performed enforcing the C 3 h symmetry. In several papers devoted to IR and Raman spectroscopies and reported by some of us, it has been shown that using the so-called anharmonic oscillator (AO) level to compute vibrations is much more accurate than the use of an ad-hoc scale factors and so for a relative weak computational cost. , , Furthermore, only full account of both mechanical and electrical anharmonicity allows us to assign the whole IR and Raman spectra (including overtones and combination bands). , So cubic and semidiagonal quartic force constants have been computed by finite differences of analytical Hessians at the B3LYP-D3 to obtain anharmonic frequencies with the GVPT2 model taking into the proper account possible Fermi and Darling–Dennison resonances, and the symmetry of the molecule. ,,, For the lowest frequencies, anharmonic contributions have been obtained using the so-called hindered rotor (HR) treatment, , which gives access to the HRAO model. , Some extra computations have also been performed using another hybrid functional, namely the MPW1PW91 in conjunction with the LANL2DZ+polarization basis set on all atoms. Hereafter, we denote this level of computation as II .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron diffraction studies of the molecular conformations have shown additional consequences: not only the proton probability density but also the orientation differs for each methyl group [12,13,14]. These deviations from the ideal symmetry have visible consequences in the Raman and IR spectra at low temperatures (< 50 K): the inactive modes for C 3h symmetry become visible whereas the previously degenerate modes E" and E" are split [15]. The influence of intra and intermolecular symmetry on the tunneling properties of the methyl groups is still more spectacular in the case of the fully hydrogenated dibromomesitylene (C 9 Br 2 H 10 or DBMH) [16].…”
Section: -Introductionmentioning
confidence: 99%
“…In our case, we applied a scaling factor of 0.98 for the frequency range 1000 -1300 cm −1 shown in the present manuscript [28]. This scaling factor corrects partly for the neglect of anharmonic corrections [29][30][31]. Most importantly, the used program allows us to fix the spin state of the system, so that in our case the calculations were conducted in both high spin and low spin states.…”
mentioning
confidence: 99%